Dual band stacked Artificial Magnetic Conductor with dipole antenna - Dewan, R. (2015)
This paper proposed a design of dual substrate layer Artificial Magnetic Conductor (AMC) which operates at operating frequency of 2.45 and 5.8 GHz. The top circular ring and the bottom rectangular AMC patch correspond to higher and lower frequency respectively. The offset effect due to distance and angular variations on the reflection phase has also been studied. The study further extended to the effect of double and quadruple circular ring AMC on the top substrate layer of stacked AMC. The dual band stacked AMC is then integrated onto two dipole antennas operating at 2.45 and 5.8 GHz band. The performance of antenna with and without AMC is observed in terms of reflection coefficient, directivity and radiation patterns.